ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR BERAS DI SULAWESI UTARA - Desiane M. Rungkat; Grace A.J. Rumagit; Charles R. Ngangi; Eyverson Ruauw (Universitas Sam Ratulangi, 2014)
ABSTRACTIncreasing the number of residents in North Sulawesi during the last three years from 2009 to 2011 led to increasing demand for rice as well. On the other hand, the production of rice in this area is not self-sufficient, so the government had to import rice to overcome the shortage of rice. The objective of this research is to identify and analyze the factors that affect the import of rice in North Sulawesi.The experiment was conducted from June to December 2013 by using secondary data obtained from the Central Bureau of Statistics, Bank Indonesia, North Sulawesi Province Food Security Agency and North Sulawesi Province Agriculture and Livestock Department in the form of a time series data in 2002-2011 period. Analysis of data use multiple linear regression methods with SPSS Statistics program version 20.Results showed that 86.5 percent of rice imports was significantly affected by the production of rice (27.8 percent significance level), consumption of the population (3.7 percent significance level), the stock of rice (4.5 percent significance level) and exchange rate (15.3 percent percent significance level), therefore it can be concluded that the increasing of rice production and rice stocks in North Sulawesi as well as an increasing in the exchange rate decreases imports of rice in North Sulawesi while the increasing consumption of the population of North Sulawesi increases imports of rice.